Factors influencing on nurses’ responses during flood disaster - Aung, Khin Thandar; Abdul Rahman, Nurul 'Inayati; Ahayalimudin, Nurul 'Ain (IOSR, 2019)
Nurses have a crucial role in any disaster situation and must respond effectively to fulfil their responsibilities. The aim of this study is to explore the factors that contribute and hinder nurses. effective responses during the flood in the East Coast region of Malaysia. An exploratory qualitative design was used in this study. Seven nurses from two hospitals were included in the semi-structured interviews who were chosen by purposive sampling and snowball sampling. Data were transcribed and analysed using thematic analysis. Four major themes emerged including accessibility of resources, knowledge about flood disaster management, support system, and willingness to participate in disaster management. As a result, there is a need to conduct flood disaster management training to prevent the possible factors that may contribute to the ineffective nursing role during flood disaster in Malaysia.